Pengembangan E-LKPD Berbasis Google Sites Terintegrasi Artificial Intelligence pada Elemen Perpajakan Siswa Kelas XII AKL - Permadhani, Reyna Mita; Rohayati, Suci (Jurnal Pendidikan Akuntansi (JPAK), 2025)
For Class XII AKL students at SMK Negeri 4 Surabaya, the purpose of this project is to create an E-LKPD based on Google Sites combined with Artificial Intelligence (AI) on taxation aspects of Value Added Tax (VAT) and Luxury Goods Sales Tax (PPnBM). Its practicality and student reactions will be examined. This development research employs Thiagarajan's 4-D model, which is restricted to the disseminate phase and comprises the define, design, develop, and disseminate phases. Questionnaires for student responses and expert validation sheets are among the tools utilized. According to validation data, the average score was 92% ("Very Eligible"), with 87.5% coming from material experts, 96% from language experts, and 93% from graphic experts. 97.75% of students answered in the "Very Understanding" category. These findings suggest that the created E-LKPD may be utilized as a cutting-edge digital learning resource that satisfies curricular requirements and contemporary technological trends.